STRENGTHENING THE ROLE OF KEUJRUEN BLANG IN IRRIGATION MANAGEMENT IN NORTH ACEH DISTRICT - Marlia Sastro; Ramziati Ramziati; Herinawati Herinawati (Universitas Syiah Kuala, 2023)
The role of Keujruen Blang in Irrigation Management for irrigating farmer's rice fields has been regulated in Aceh Qanun Number 10 of 2008 and the Governor's Regulation. Number 45 of 2015 concerning the Role of Keujruen Blang in Irrigation Management. However, the implementation of Keujruen Blang's role in irrigation management in North Aceh District has not been fully implemented as stipulated in the regulations. This study aims to realize the role of Keujruen Blang in the irrigation management of farmer’s rice fields and to scrutinize the strengthening of the role of Keujruen Blang as stipulated in the rules as a traditional institution whose job is to help farmers to obtain water for irrigating their fields. This study used empirical juridical research with a qualitative approach. The main data were collected by interviewing respondents and informants. Secondary data were obtained by reviewing current and related literature. The result shows that the role of Keujruen Blang in irrigation management to irrigate rice fields has not been implemented in accordance with the Qanun and Aceh Governor's Regulation. The obstacles in the implementation of the duties, functions, and authorities of Keujreun Blang among others are Keujreun Blang does not know and fully understand their functions, roles, and authorities yet; poor water discharge management due to limited availability of water discharge; inadequate infrastructure; lack of socialization carried out by the government about the role and function of Keujrun Blang. Therefore, in order to strengthen the role of Keujruen Blang in irrigation management needs to conduct coaching and socializing the duties, functions, and roles of Keujruen Blang in accordance with Qanun and the Governor Regulations; and involve Keujruen Blang in the irrigation management process started from the stage of policy planning, implementation, to supervision so that they can provide recommendations needed by villages regarding irrigation management to irrigate rice fields.